PKM Kelompok Dasawisma di Kelurahan Kenali Asam Bawah - Tina Yuli Fatmawati; Ariyanto Ariyanto; Dinda Anjani Putri (Jurnal Abdimas Kesehatan (JAK), 2020)
The healthy living community movement (GERMAS) aims to increase awareness, willingness and the ability of people to behave in an effort to improve the quality of life. GERMAS is carried out as a reinforcement of community promotive and preventive efforts. Some observations made on the dasawiwma group do not have a family medicinal plant (TOGA) yet, partners are very hopeful that the provision of health education to the dasawisma group in order to better understand the benefits of TOGA. This dedication activity has been carried out in Kenali Asam Bawah Kelurahan with the target of dasawisma and the community, carried out in Juny 2019. Through this service the team facilitated, assisted the homeless and residents in identifying, identifying, and coping with public health problems. The team also helped prepare toga, demonstrations in making drinks from celery and soursop leaves, Provision of posters / booklets